Diagnosis of rabies and eastern and western equine viral encephalitides in equids by multiplex hemi-nested RT-PCR technique - Iamamoto, K.; Durymanova, E. A.; Carrieri, M. L.; Oliveira, R. N.; Carnieli Jr, P.; Fahl, W. O.; Kotait, I.; Silva, M. L. C. R.; Castilho, J. G.; Ito, F. H. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Several viral zoonoses affect the equids causing neurological diseases, including rabies and Eastern and Western equine encephalitides (EEE and WEE). Clinical diagnosis is often not conclusive, in a way that laboratory diagnosis is essential. Data from the Laboratory of Rabies Diagnosis at the Pasteur Institute of São Paulo, between 2000 and 2010, demonstrate that approximately 75% of submitted equid samples, wich animals presented neurological symptoms, were negative for rabies, emphasizing the importance of achieving a differential diagnosis for equine encephalitis caused by alphaviruses. The aim of this study was to test the suitability of using multiplex hemi-nested RT-PCR for the diagnosis of rabies, EEE and WEE in equids central nervous system samples. We used the primers 21G, 304 and 504 directed to the N gene of rabies virus, and the primers cM3W, M2W, nEEE and nWEE directed the NSP1 gene of WEE and EEE viruses. A preliminary study of the primers was carried out, as well as their use in a hemi-nested RT-PCR, evaluating the optimal annealing temperature, the analytical sensitivity and specificity and the reproducibility of the technique in positive field samples for rabies and EEE. Based on the established protocol for the hemi-nested RTPCR, variations in reagents concentrations for the multiplex hemi-nested RT-PCR protocol were perfomed. After establishing the protocol for this reaction, the tests to verify the analytical sensitivity and specificity and reproducibility were performed and the results were compared to those obtained by hemi-nested RT-PCR. In the detection threshold test, the analytical sensitivity was similar for both techniques, resulting in 10- 1.7 for the three standard virus CVS, EEEV and WEEV. In the detection threshold test using a sample with the three viruses, a high specificity of the primers was verified and the multiplex hemi-nested RT-PCR was able to detect the three viruses simultaneously. There was no difference in the proportions of samples detected as positive for rabies obtained by both techniques, according to the Fisher exact test (P = 1.0000). However, for EEE positive field samples, the proportion of samples detected as positive by the hemi-nested RT-PCR a difference in the proportion obtained by multiplex hemi-nested RT-PCR (P